SENSITIVITAS KELAYAKAN FINANSIAL PENGOLAHAN KOPI BUBUK - Romdhon, Muhammad Mustopa; Andani, Apri; Ayu, Adinda Merizka (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2018)
Kepahiang district is one of the Robusta’s coffee production centre in Bengkulu Province. With total area size of Robusta coffee about 454.073 hectares, the production was about 1, 2 million ton in a year. The production is available for more than 30 local coffee processor at Kabupaten Kepahiang. A great contribution to an economy, robusta coffee processors were providing jobs, market guarantees and added value. Today, the ninety percent of production was delivered to outside processors while only ten percent was for local processors. The business, its self-facing fluctuation of output and input prices, highest risk, interest rate, and etc. How was the sensitivity level of the financial feasibility of coffee processor at Kepahiang district? Financial feasibility sensitivity level was assessed by the three changing indicators namely input availability, interest rate and input cost. The results show that business of coffee processor at Kepahiang district is still profitable and feasible under the three changing indicators.